Online evaluation system for student's project - Ismail, Khairil Izwani (Faculty of Computer and Mathematical Sciences, 2007)
The conventional way of using paper to evaluate students' project is time consuming. This is because the evaluators have to fill in several forms and the data need to be assembled in order to calculate the overall marks from each evaluator. This process seems tedious and cannot be done at the evaluators convenience.Centralizing data to databases is more efficient for storing data. The database must be integrated with a system that can capture data, performing calculation and store them to the database.This is where the development of an online evaluation system is needed for this task. On the other hand, other issues arise such as type of software should be used in the development process, the realibility of free software (open source) for software development, enhancements from the current evaluation system if exist and the realibility of the evaluation system itself if it is implemented in the real situation. The solutions to all these problems are among the objectives of this project. The development of the system follows the sofware engineering methodology called software process model that cover every aspect of software development of this system from identifying requirements until the maintenance part. Beta testing is one of the requirements of this system to measure the capability of the evaluation system itself as well as the open source sofware used for the development process. As a result from the activities which have been through, the feedback from users towards the system are gathered and a final product of working prototype is obtained from this project called 'Electronic Evaluation System for Student Project' or e-EvaSP. As it is called prototype, the system is continually refined and rebuilt.